A facile synthetic route to tungsten diselenide using a new precursor containing a long alkyl chain cation for multifunctional electronic and optoelectronic applications. Issue 11 (20th February 2019) - Kim, Jahee; Lim, Yi Rang; Yoon, Yeoheung; Song, Wooseok; Park, Bo Keun; Lim, Jongsun; Chung, Taek-Mo; Kim, Chang Gyoun
Abstract : Single source precursors for coating and subsequent thermal decomposition processes enable a large-scale, low-cost synthesis of two-dimensional transition metal dichalcogenides (TMDs). Abstract : Single source precursors for coating and subsequent thermal decomposition processes enable a large-scale, low-cost synthesis of two-dimensional transition metal dichalcogenides (TMDs). However, practical applications based on two-dimensional TMDs have been limited by the lack of applicable single source precursors for the synthesis of p-type TMDs including layered tungsten diselenide (WSe2 ). We firstly demonstrate the simple and facile synthesis of WSe2 layers using a newly developed precursor that allows improved dispersibility and lower decomposition temperature. We study the thermal decomposition mechanism of three types of (Cat + )2 [WSe4 ] precursors to assess the most suitable precursor for the synthesis of WSe2 layers. The resulting chemical and structural exploration of solution-processed WSe2 layers suggests that the (CTA)2 [WSe4 ] may be a promising precursor because it resulted in the formation of high-crystalline WSe2 . In addition, this study verifies the capability of WSe2 layers for multifunctional applications in optoelectronic and electronic devices. The photocurrent of WSe2 -based photodetectors shows an abrupt switching behavior under periodic illumination of visible or IR light. The extracted photoresponsivity values for WSe2 -based photodetectors recorded at 0.5 V correspond to 26.3 mA W −1 for visible light and 5.4 mA W −1 for IR light. The WSe2 -based field effect transistors exhibit unipolar p-channel transistor behavior with a carrier mobility of 0.45 cm 2 V −1 s −1 and an on-off ratio of ∼10.